Cybersecurity Awareness as a Component of HR Policies: Protecting Employee and Organizational Data in the Digital Era - Inpaeng Sayvaya; Mei Veronika Siagian (Takaza Innovatix Labs Ltd., 2025)
Cybersecurity awareness has become a critical organizational priority in the digital era, where human factors play a significant role in mitigating cyber risks. This study investigates the implementation of cybersecurity awareness policies within human resource (HR) management, focusing on their effectiveness, challenges, and potential solutions. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis in organizations with established HR policies addressing cybersecurity. The findings reveal that tailored training programs, leadership support, and cross-departmental collaboration are key to fostering employee engagement and preparedness. However, challenges such as resource limitations, resistance to change, and rapidly evolving cyber threats hinder the effectiveness of these initiatives. The study underscores the importance of aligning cybersecurity awareness with organizational culture and leveraging innovative approaches, such as gamification and role-specific training, to enhance engagement. This research contributes to the existing body of knowledge by exploring the intersection of HR policies and cybersecurity and provides actionable insights for organizations to strengthen their resilience. Recommendations for future research include examining the long-term impact of cybersecurity awareness programs and exploring their applicability across diverse organizational contexts.